2005
DOI: 10.1083/jcb.200501071
|View full text |Cite
|
Sign up to set email alerts
|

Inducible ablation of mouse Langerhans cells diminishes but fails to abrogate contact hypersensitivity

Abstract: Langerhans cells (LC) form a unique subset of dendritic cells (DC) in the epidermis but so far their in vivo functions in skin immunity and tolerance could not be determined, in particular in relation to dermal DC (dDC). Here, we exploit a novel diphtheria toxin (DT) receptor (DTR)/DT-based system to achieve inducible ablation of LC without affecting the skin environment. Within 24 h after intra-peritoneal injection of DT into Langerin-DTR mice LC are completely depleted from the epidermis and only begin to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
472
4
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(506 citation statements)
references
References 35 publications
25
472
4
3
Order By: Relevance
“…Recently, three different groups reported three distinct results of CHS response by transient depletion of LC using mice that express diphtheria toxin receptor on LC; that is, (i) diminished (but not abrogated) [43], (ii) enhanced [44], and (iii) unchanged CHS response [45]. Thus, LC may not be the only cells that are required for the induction of CHS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three different groups reported three distinct results of CHS response by transient depletion of LC using mice that express diphtheria toxin receptor on LC; that is, (i) diminished (but not abrogated) [43], (ii) enhanced [44], and (iii) unchanged CHS response [45]. Thus, LC may not be the only cells that are required for the induction of CHS.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that LC are dispensable for the induction of CHS responses. In contrast, Dutch Langerin-DTR-EGFP mice treated with DT 3 days prior to sensitization developed diminished but not absent CHS in response to a standard dose of another hapten, trinitrochlorobenzene, suggesting that LC are required for optimal initiation of CHS responses [29]. Finally, the American Langerin-DTA mice, constitutively lacking LC, developed enhanced CHS responses compared with littermate controls to both DNFB and a third hapten, oxazalone [31].…”
Section: Generation Of Three Lc-deficient Mouse Modelsmentioning
confidence: 96%
“…The Dutch group targeted a DTR-EGFP cassette into the second exon of the langerin gene [29]. The French group generated two separate lines in which either an IRES-EGFP or an IRES-DTR-EGFP cassette was knocked-in to the sixth exon, in the 3 0 -untranslated region of langerin [30].…”
Section: Generation Of Three Lc-deficient Mouse Modelsmentioning
confidence: 99%
“…Efficient immunosurveillance in the skin is based upon the continuous traffic of cells from the skin to the draining lymph nodes. Although Langerhans cells (LCs) have been shown to be potent APCs in vitro [3], in vivo approaches have produced conflicting data regarding their role in T-cell priming [4,5]. Dermal DCs are also migrating DCs that colonize lymph nodes more rapidly than LCs [6,7], and different roles for skin DC subsets in T-cell priming have been reported [7][8][9].…”
Section: Introductionmentioning
confidence: 99%